Challenges of New Technologies in the Field of Criminal Law. The Protection of the Right to Privacy in the Spanish Penal Code. - García-Magna, Débora (My University, 2018)
The use of new technologies has become widespread in the last decade, giving rise to various risks associated with the transfer of personal data and the publication of sensitive material on social media. There are already several supranational instruments that seek to protect the citizens involved in this growing traffic of personal information and, especially, the most vulnerable people, such as minors, who are also the ones who make the most intense use of these new means of communication. In this sense, the configuration of the concept of privacy as a legal right has necessarily been influenced by these new social uses and supranational instruments. The researcher considers correct the decision to introduce sexting as a new criminal behaviour in the Penal Code in 2015, but questions the concrete manner in which it has been made. To this end, an updated review of the various options that our legal system already offered is made, assessing whether these legal options adequately addressed the new social needs and guidelines from jurisprudence and other supranational instruments. Some important issues emerge as to whether the principles of fragmentarity and subsidiarity may be violated, since the new article 197.7 of the Spanish Penal Code could refer to very varied behaviours and protect not only particularly vulnerable persons. In this sense, the research focuses on issues such as the concept of "seriousness" of the infringement of privacy, the possible reckless conduct of the victim, who hang over its own private material to third parties, the affection to other legal rights such as freedom and sexual indemnity, the possible problems of concurrent offences, etc.
Keywords: Derecho a la intimidad; Criminal law reform; ECHR jurisprudence; Right to privacy; Sexting